KONSTRUKSI MANAJEMEN KEREDAKSIAN DUNIA NEWS DALAM MENGELOLA JURNALISME WARGA (CITIZEN JOURNALISM) - Helen Vanhurk Sriwati Ningsih Sitorus; Prietsawenny RT Simamora; April Yanus Harefa (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2021)
This study aims at finding out the construction of editorial management in the world of news in managing citizen journalism and to analyze the construction process of editorial management in the world of news in managing citizen journalism. The method applied by the researcher is a descriptive method with a qualitative approach, in which the researcher uses qualitative data analysis based on the results of interviews with informants or people who are directly related to this research. The findings in the field, this research states the existence of citizen journalism as a news reporter. modern journalism. It is emphasized that media journalism activities are no longer carried out by a journalist who has the profession of a journalist but a citizen or someone who wants to write news and is talented can also become a good journalist. Supported by sophisticated media and well packaged information make journalism activities more modern, citizen journalism is a reflection of society's expression in the future in the world of journalism. Currently, many people use camera applications and video recordings on their cell phones. Through this application, all the desired news can be obtained and delivered quickly without any interference from the media